Trystan Horne

2022-02-04

How do you simplify $5xy-6{x}^{2}{y}^{2}=4{x}^{2}{y}^{2}-2xy?$

Pecsan9mj

Beginner2022-02-05Added 13 answers

Step 1

First, group and combine like terms:

$5xy-6{x}^{2}{y}^{2}+4{x}^{2}{y}^{2}-2xy\Rightarrow$

$-6{x}^{2}{y}^{2}+4{x}^{2}{y}^{2}+5xy-2xy\Rightarrow$

$(-6+4){x}^{2}{y}^{2}+(5-2)xy\Rightarrow$

$-2{x}^{2}{y}^{2}+3xy$

Now, factor an$xy$ out of each term:

$(xy\times -2xy)+(3\times xy)\Rightarrow$

$xy(-2xy+3)$

First, group and combine like terms:

Now, factor an

Pamela Webb

Beginner2022-02-06Added 10 answers

Step 1

You would collect equal variables together

$(5xy-2xy)+(-6{x}^{2}{y}^{2}+4{x}^{2}{y}^{2})$

Simplify it

$5xy-2xy=3xy$

$-6{x}^{2}{y}^{2}+4{x}^{2}{y}^{2}=-2{x}^{2}{y}^{2}$

$3xy-2{x}^{2}{y}^{2}$

Factorise it by taking a common factor which is$-xy$

$-xy(2xy-3)$

You would collect equal variables together

Simplify it

Factorise it by taking a common factor which is